An Empirical Analysis of why the WTO is Broken and cannot be Fixed – yet - Drache, Daniel; Froese, Marc (Eurostudia, 2007)
AbstractThis article empirically examines the WTO’s dispute settlement performance over the past decade. Dispute settlement is the most significant deliverable of WTO governance and embodies all that is both problematic and progressive about that international institution. The article analyzes a number of important and unforeseen institutional consequences of the shift from an informal GATT mechanism to the mandatory norms and processes of WTO litigation. The rise to prominence of antidumping trade remedy action, a retaliatory dynamic of dispute settlement and the continued dominance of developed countries at the Dispute Settlement Mechanism (DSM) has contributed greatly to the current negotiating deadlock.